The Ten commandments : the significance of God's laws in everyday life - Schlessinger, Laura; Vogel, Stewart (New York, NY : Cliff Street Books, 1998)
Talk radio personality Dr. Laura Schlessinger teams up with Rabbi Stewart Vogel to discuss the relevance of God's ten commandments on everyday life in the late twentieth century.
Keywords: Ten commandments; Conduct of life